Observation of the associated production of a single top quark and a W boson in pp collisions at sqrt[s] = 8 TeV. - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (APS, 2014)
The first observation of the associated production of a single top quark and a W boson is presented. The analysis is based on a data set corresponding to an integrated luminosity of 12.2fb-1 of proton-proton collisions at s=8TeV recorded by the CMS experiment at the LHC. Events with two leptons and a jet originating from a b quark are selected. A multivariate analysis based on kinematic and topological properties is used to separate the signal from the dominant tt̄ background. An excess consistent with the signal hypothesis is observed, with a significance which corresponds to 6.1 standard deviations above a background-only hypothesis. The measured production cross section is 23.4±5.4pb, in agreement with the standard model prediction. © 2014 CERN, for the CMS Collaboration.

National Natural Science Foundation of China

Massachusetts Department of Fish and Game

Science and Technology Facilities Council

Russian Foundation for Basic Research

Canadian Anesthesiologists' Society

Neurosurgical Research Foundation

National Science Council Taiwan

National Institutes of Health

Research Promotion Foundation
Keywords: p p: scattering; data analysis method; p p --> top W anything; top: single production; General Physics and Astronomy; Physics; Physics and Astronomy (all); info:eu-repo/classification/ddc/530; Detector; Fisica delle particelle; PRODUCTION CROSS-SECTION; Detector; Physics; Atlas; LHC; GeV-cms; info:eu-repo/classification/ddc/550; background; CMS; Physics; dilepton: final state; ddc:530; Atlas; Top quark; PRODUCTION CROSS-SECTION; CERN LHC Coll; W boson; Medicine (all); Physics and Astronomy (all); LHC; W: associated production; jet: bottom; channel cross section: measured; experimental results